Perceptions of Anticipated Stigma in Gay and Lesbian Workers in Health Services (Argentina) - Ortega, Julián (CIICLA, Universidad de Costa Rica, 2020)
Este documento es una traducción al inglés del artículo original "Percepciones del estigma anticipado en trabajadores/as gays y lesbianas del sector salud (Argentina)" publicado en este mismo número. This article analyses situations of discrimination, violence and inequality against gay and lesbian workers due to their sexual orientation, gender and / or gender expression in healthcare institutions located in the Metropolitan Area of Buenos Aires. Some of the qualitative findings of a larger study are developed, which had a mixed approach and a cross-sectional, non-experimental design, in order to describe variants of anticipated stigma and perceptions of sexual orientation as potential obstacle at work. The persistence of stigma toward gay and lesbian workers, despite the greater legal and social recognition these groups have gained over the past decades, is a theoretical assumption of the study. While favourable changes are recognized, it is concluded that anticipated stigma persists among this group of workers.